Interleukin-1β rs16944 and rs1143627 polymorphisms and risk of developing major depressive disorder: A case-control study among Bangladeshi population - Faria Mehreen Toma; Khondoker Tashya Kalam; Md. Aminul Haque; Sejuti Reza; Raushanara Akter; Mohammad Safiqul Islam; Md. Rabiul Islam; Zabun Nahar (PLoS ONE, 2025)
Background Epidemiological research suggests that altered levels of cytokine are associated with pathophysiology and the development of major depressive disorder (MDD). Based on earlier study, IL-1β rs16944 and rs1143627 polymorphisms may increase the risk of depression. Here, we aimed to evaluate the correlation between these polymorphisms and MDD susceptibility among the population in Bangladesh. Methods Blood samples were collected from 100 MDD patients and 70 matched controls. Study participants were evaluated by DSM-5 criteria and PCR-RFLP method were applied for genotyping. Results The IL1β rs1143627 and rs16944 polymorphisms were found to have a significant association with the risk of MDD. In case of rs1143627 CT heterozygous genotype (OR = 2.22, 95% CI = 1.08–4.55, p-value = 0.029) and combined CT+TT (OR = 2.35, 95% CI = 1.15–4.79, p-value = 0.019) genotype was strongly associated with the increased risk of MDD in comparison to CC common genotype. Moreover, the over-dominant model indicated a 2.15-fold higher risk for MDD development (OR = 2.15, 95% CI = 1.05–4.40, p-value = 0.036). On the other hand, the IL1β rs16944 polymorphisms revealed that the TC+CC combined genotype in the dominant model showed a 2.06-fold increased risk for MDD development compared to the TT common homozygote (OR = 2.06, 95% CI = 1.06–3.99, p-value = 0.032). Conclusion Studies suggests that IL1β rs16944 and rs1143627 polymorphisms are associated with an increased risk of MDD. These findings will provide us with valuable insights into the pathophysiology of MDD.